Prediction of the Collapse Region Induced by a Concealed Karst Cave above a Deep Highway Tunnel - Fu Huang; Di Wang; Yuan Feng; Min Zhang (Advances in Civil Engineering)
The presence of a concealed karst cave above a deep highway tunnel may cause the collapse of the rock mass between the karst cave and tunnel during excavation. Rock mass collapse threatens the safety of tunnel construction personnel. A prediction method of the collapse region induced by a concealed karst cave above a deep highway tunnel is proposed on the basis of the upper bound theorem of limit analysis. An analytical expression of the collapse surface is derived from the variational principle. Using the analytical expression of the collapse surface, the shapes of the collapse surfaces are plotted for different rock mass parameters. Moreover, the minimum safe distance between the karst cave and tunnel is defined, and the computational equation of the minimum safe distance is derived. The proposed method is applied in a highway tunnel excavated in a karst terrain as a case study. Based on geological survey report parameters, the shape of the collapse surface and the minimum safe distance between the karst cave and tunnel are obtained. Finally, the collapse surface of the rock mass provided by the proposed approach is compared with that provided by numerical simulation, and the favorable result comparison shows that the proposed method is valid.